Male and Female Perceptions and Experiences of Sexual and Gender-based Violence in South Kivu, Eastern DRC - Thulin, Elyse J. (Journal of interpersonal violence, 2022)
Conflict settings are often the context of some of the highest rates of sexual and gender-based violence (SGBV). Although women are disproportionately the victims of SGBV, they are not the only victims. Indirect impacts of SGBV also impact men, families, and communities. Examining SGBV as only a woman?s concern reinforces the hegemonic gender-binary view that SGBV somehow does not include men, who can be direct victims of SGBV, family members of female victims of SGBV, and/or perpetrators of SGBV. This qualitative study seeks to fill a gap by exploring the impact of SGBV on individuals, families, and communities, and potential options to ameliorate those issues. Data were collected in 2019 from community-based discussions in South Kivu, Democratic Republic of Congo. Women described being direct victims of SGBV, as well as the burden of being at constant alert to the possible threat of violence. Men talked more about SGBV being perpetrated against women, and the indirect effect on men?s perception of their social husband and/or father role to protect and provide for their family. Taken together, women and men describe three types of violence: sexual violence by an unknown assailant who is often associated the rebel groups or the military; sexual violence from a known assailant within one?s community; and sexual or physical violence within intimate partnerships (i.e., intimate partner violence). Women focused more on community-based solutions to reduce their exposure to violence, while men discussed the government?s responsibility to end the long-standing conflict that has severely disrupted lives. Practically, these findings support the need to specify different types of SGBV, and the opportunity to tailor interventions by type.